Motivations for youth migration from rural to urban areas in Brazil - Gomes da Rocha Junior, Claudio Jorge (2023)
The Brazilian rural environment, in which 15% of the country's population is distributed, is marked by heterogeneous and not always favorable realities in relation to the fundamental rights established in the constitution. Consequently, how would it be possible for rural young people to transition to adulthood in their own places of origin, without the need or willingness to migrate? What encourages their rural exodus? Do they have opportunities to express their desires and thus fully seek the state of human development? This paper was developed through a narrative literature review, including contemporary sociological authors and scientific papers related to Brazilian rural youth. A content analysis technique was used, which brought opportunities for scientific investigation. The study included a debate on rural youth, schooling, political participation, management, family succession, youth protagonism, and above all, it identified the factors that stimulate rural youth migration in Brazil.